PP47 The Cost of Overweight and Obesity on the Island of Ireland. (10th September 2013) - Dee, A P; Perry, I J; O'Neill, C; Doherty, E; Callan, A; Kearns, K; O'Dwyer, V; Staines, A; McVeigh, T; Sweeney, M R; Sharp, L; Balanda, K; et al.
Abstract : Background: Overweight and obesity are increasing in prevalence worldwide In Ireland, their prevalence makes up over 60% of the population. The incidence of many chronic diseases, and some cancers, is increased in those who are overweight and obese. This places pressure on the health service, financially and otherwise. There is also a cost on society in terms of productivity loss. Many countries have studied the costs involved, but as each country has a unique profile of risk prevalence and health service, the costs are country specific. In order to inform prevention policies and ignite political will in the public health battle against obesity, the measurement of direct and indirect costs of overweight and obesity is a useful exercise. This study was a collaborative effort to enumerate these costs for the island of Ireland. Methods: A comprehensive literature review was performed examining the international evidence on cost of overweight and obesity. Regression analyses of data from SLAN and TILDA in the Republic of Ireland, and The 2010/11 Health Survey for Northern Ireland were performed to give estimates of direct health care costs in both jurisdictions, and of indirect costs due to absenteeism. In addition, Population Attributable Fractions were applied to hospital activity, drug reimbursement, social welfare and mortality data for both jurisdictions to give additional information where no survey data were available, and to triangulate results. Adjustments were made for inflation and purchasing power parity to allow for the production of an estimate in one currency for a single year. Results: The literature review yielded 45 studies and showed heterogeneity of methodology between studies. However, in almost all cases there was a positive correlation between obesity and increased healthcare costs, and indirect costs were in all cases greater than direct costs. The cost of overweight and obesity for the Republic of Ireland was estimated to be €1, 166, 050, 482 and for Northern Ireland it was €510, 323, 754 for the year 2009. Direct healthcare costs represented 38% of the total, and 2.9% of total healthcare spend in the Republic of Ireland and, in Northern Ireland, 25% of the total and 2.8% of total healthcare spend. Conclusion: Urgent public health action is required in Ireland to address the problem of increasing prevalence of overweight and obesity. The cost of associated chronic disease is substantial, and if prevalence rates continue to rise, will cause unsustainable health service cost escalation, and productivity losses to the wider economy.